Maternal High-Fructose Intake Activates Myogenic Program in Fetal Brown Fat and Predisposes Offspring to Diet-Induced Metabolic Dysfunctions in Adulthood - Wang, Peng; Wu, Tian; Fu, Qinghua; Liao, Qichao; Li, Yan; Huang, Tengda; Li, Yixing; Zhou, Lei; Song, Ziyi (Frontiers in Nutrition, 2022)
Excess dietary fructose intake is a major public health concern due to its deleterious effect to cause various metabolic and cardiovascular diseases. However, little is known about the effects of high-fructose consumption during pregnancy on offspring metabolic health in adulthood. Here, we show that maternal consumption of 20% (w/v) fructose water during pregnancy does not alter the metabolic balance of offspring with a chow diet, but predisposes them to obesity, fatty liver, and insulin resistance when challenged by a high-fat diet. Mechanistically, diet-induced brown fat reprogramming and global energy expenditure in offspring of fructose-fed dams is impaired. RNA-seq analysis of the fetal brown fat tissue reveals that the myogenic pathway is predominantly up-regulated in fructose-treated group. Meanwhile, circulating fructose level is found to be significantly elevated in both fructose-fed dams and its fetuses. Importantly fructose gavage also acutely activates myogenic program in mice brown fat. Together, our data suggest that maternal high-fructose intake impairs fetal brown fat development, resultantly attenuates diet-induced thermogenesis and causes metabolic disorders in adult offspring probably through inducing myogenic signature in brown fat at the fetal stage.